ANALISIS STRATEGI PEMASARAN UNTUK MENINGKATKAN HUNIAN KAMAR DI ANANTARA ULUWATU BALI RESORT - Ida Ayu Trisna Wijayanthi; Putu Mela Ratini; Ni Ketut Pradnyadari (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2020)
The rapid development of tourism in Bali has an impact on the rapid growth of accommodation facilities as well. The mushrooming of various types of accommodation has an impact on the very high competition in the accommodation business. As one of the five-star hotels in Bali, Anantara Uluwatu Bali Resort has a department that specializes in promoting and selling all the hotel's main products, namely the Sales and Marketing department. Sales and Marketing departments have very high sales targets, this target will rise 5% from the reality each year, which is based on historical data of the company's sales. For this reason, the Sales and Marketing department has a marketing strategy aimed at increasing hotel sales volume. The purpose of this study is to describe and analyze effective marketing strategies in increasing the volume of room sales at Anantara Uluwatu Bali Resort. The samples taken were 61 consisting of top management to middle management of Anantara Uluwatu Bali Resort using the Slovin technique. The data analysis method used in this study is a SWOT analysis based on the company's internal and external environment. The results showed that Anantara Uluwatu Bali Resort was a company that implemented a marketing strategy that differentiated the market (differentiated marketing) with the type of entrepreneurs who segmented the market. In its generic strategy the company uses an expansion strategy and applies the 7P marketing mix concept to its daily marketing activities. The results also show that to increase effective sales volume, companies must use and implement an aggressive growth strategy by developing and utilizing the strengths and opportunities (SO) of Anantara Uluwatu Bali Resort for business development.